The relationship of serum IL-17 and IL-21 levels and TRUST titer in syphilis patients with positive serological test - Rong ZHANG; Dongping LU; Fen WANG; Jie JIA; Weilian ZHANG; Wenzhi YANG; Bingyan LI; Ting LIU (Pifu-xingbing zhenliaoxue zazhi, 2021)
Objective: To explore the immune mechanism of syphilitic sero-fixation by measuring the expression levels of serum IL-17 and IL-21 in syphilis patients with positive serological test. Methods: Subjects included syphilitic sero-fixation, syphilis with Toluidine red unheated serum test (TRUST) negative, early syphilis, and normal healthy controls, 30 subjects per groups. Serum concentrations of IL-17 and IL-21 were measured by ELISA, while TRUST titers were measured with TRUST kit. The differences in serum IL-17 and IL-21 levels were compared among four groups. Pearson correlation analysis was used to analyze the correlation between TRUST titers and IL-17 and IL-21 levels. Results: The serum levels of IL-17 [(25.43±4.58) pg/mL]and IL-21[(36.14±6.54) pg/mL] in early syphilis group were significantly higher than that in the other three groups (P<0.05). The concentrations of serum IL-17 [(8.84±1.46) pg/mL] and IL-21[(16.52±5.84) pg/mL]in syphilitic sero-fixation group were lower than those in both healthy controls [IL-17: (11.52±2.51) pg/mL; IL-21: (21.56±5.38) pg/mL] and the TRUST negative subjects [IL-17: (11.64±2.49) pg/mL; IL-21: (21.05±5.16) pg/mL](P<0.05), but were not comparable between the healthy controls and TRUST negative subjects (P>0.05). The serum levels of IL-17 and IL-21 were correlated positively with TRUST titers in the early syphilis patients (r=0.75, 0.62, respectively, both P<0.05), but not in syphilitic sero-fixation patients (r=0.22, 0.15, respectively, both P>0.05). Conclusions: Both IL-17 and IL-21 are involved in the syphilis immune process in early syphilis. The formation of syphilitic sero-fixation could be associated with decreased serum levels of IL-17 and IL-21, but not TRUST titers.